2020
DOI: 10.1186/s12887-020-02051-7
|View full text |Cite
|
Sign up to set email alerts
|

Cause and predictors of neonatal mortality among neonates admitted to neonatal intensive care units of public hospitals in eastern Ethiopia: a facility-based prospective follow-up study

Abstract: Background: The first month is the most crucial period for child survival. Neonatal mortality continues to remain high with little improvement over the years in Sub-Saharan Africa, including Ethiopia. This region shows the least progress in reducing neonatal mortality and continues to be a significant public health issue. In this study setting, the causes and predictors of neonatal death in the neonatal intensive care units are not well documented. Hence, this study aimed to determine the causes and predictors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 26 publications
16
41
0
1
Order By: Relevance
“…Although inferior to an antenatal ultrasound scan, assessment based on date of last menstrual period, the most common method in our study, has been shown to be relatively reliable for the estimation of gestational age in LMICs [ 38 ]. Our findings are consistent with the multivariable logistic regression analysis in the prospective studies in Ethiopia, where both gestation <37 weeks and LBW were independently associated with mortality in the multicentre study [ 21 ] and gestational age below mean value (<36.6 weeks) in the single centre study [ 22 ]. In our analysis and the study by Desalaw et al ., although not mutually exclusive, both prematurity and LBW were retained in the multiple regression model suggesting that preterm birth and intra-uterine growth restriction independently increase the risk of mortality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although inferior to an antenatal ultrasound scan, assessment based on date of last menstrual period, the most common method in our study, has been shown to be relatively reliable for the estimation of gestational age in LMICs [ 38 ]. Our findings are consistent with the multivariable logistic regression analysis in the prospective studies in Ethiopia, where both gestation <37 weeks and LBW were independently associated with mortality in the multicentre study [ 21 ] and gestational age below mean value (<36.6 weeks) in the single centre study [ 22 ]. In our analysis and the study by Desalaw et al ., although not mutually exclusive, both prematurity and LBW were retained in the multiple regression model suggesting that preterm birth and intra-uterine growth restriction independently increase the risk of mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Variability in mortality between NNUs was marked and ranged between 4.0–28.0%. Mortality in our study is consistent with prospective studies of admissions to six NNUs in public hospitals in Eastern Ethiopia (mortality of 20.0%) [ 21 ] and to a public teaching hospital in Addis Ababa, Ethiopia (23.1%) [ 22 ]. In retrospective studies, mortality ranged from 13–38% in NNUs in Kenya [ 29 , 30 ], 5.7–23.3% in Ethiopia [ 23 , 24 ], 18.8% in Nigeria [ 25 ], 15.7% in Cameroon [ 26 ] and 8.2% in Eritrea [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…Health service utilization during pregnancy and child birth minimize neonatal death due to those preventable conditions, similarly in this study, the odds of death among newborns that had low birth weight were 4.01 times that of neonates who did not have the conditions. This is consistent with studies conducted in Brazil, Guinea-Bissau, Eritrea, Jimma, and eastern Ethiopia [ 1 , 5 , 9 , 13 , 21 ]. The possible justification is that in fact that low birth weight had immaturity of immune systems and, other body defense mechanisms that control newborn disease susceptibility [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our nding is in line with Titaley's report, which elucidated higher odds of women experiencing the death of their neonates in public hospitals than in private hospitals (32). Based on a report in Ethiopia, the rate of neonatal deaths in public hospitals was in uenced mostly by preterm birth, birth asphyxia and neonatal infection (38). In addition, Adams et al suggested that a disparity exists between the ability to alleviate the burden of the neonatal mortality rate in public hospitals and private hospitals, in which public hospitals demonstrated a higher rate of neonatal deaths.…”
Section: Discussionsupporting
confidence: 90%